Functionality and feedback: a protocol for a realist synthesis of the collation, interpretation and utilisation of PROMs data to improve patient care. Issue 7 (22nd July 2014) - Greenhalgh, Joanne; Pawson, Ray; Wright, Judy; Black, Nick; Valderas, Jose Maria; Meads, David; Gibbons, Elizabeth; Wood, Laurence; Wood, Charlotte; Mills, Chris; Dalkin, Sonia
Abstract : Introduction: The feedback and public reporting of PROMs data aims to improve the quality of care provided to patients. Existing systematic reviews have found it difficult to draw overall conclusions about the effectiveness of PROMs feedback. We aim to execute a realist synthesis of the evidence to understand by what means and in what circumstances the feedback of PROMs data leads to the intended service improvements. Methods and analysis: Realist synthesis involves (stage 1) identifying the ideas, assumptions or 'programme theories' which explain how PROMs feedback is supposed to work and in what circumstances and then (stage 2) reviewing the evidence to determine the extent to which these expectations are met in practice. For stage 1, six provisional 'functions' of PROMs feedback have been identified to structure our review (screening, monitoring, patient involvement, demand management, quality improvement and patient choice). For each function, we will identify the different programme theories that underlie these different goals and develop a logical map of the respective implementation processes. In stage 2, we will identify studies that will provide empirical tests of each component of the programme theories to evaluate the circumstances in which the potential obstacles can be overcome and whether and how the unintended consequences of PROMs feedback arise. We will synthesise this evidence to (1) identify the implementation processes which support or constrain the successful collation, interpretation and utilisation of PROMs data; (2) identify the implementation processes through which the unintended consequences of PROMs data arise and those where they can be avoided. Ethics and dissemination: The study will not require NHS ethics approval. We have secured ethical approval for the study from the University of Leeds (LTSSP-019). We will disseminate the findings of the review through a briefing paper and dissemination event for National Health Service stakeholders, conferences and peer reviewed publications.